GMP-Compliant Production of Autologous Adipose-Derived Stromal Cells in the NANT 001 Closed Automated Bioreactor - Fitzgerald, Joan C.; Duffy, Niamh; Cattaruzzi, Giacomo; Vitrani, Francesco; Paulitti, Alice; Mazzarol, Flavia; Mauro, Prisca; Sfiligoj, Antonio; Curcio, Francesco; Jones, Deirdre M.; McInerney, Veronica; Krawczyk, Janusz; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years mesenchymal stromal cells (MSCs) have received a great deal of interest for the treatment of major diseases, but clinical translation and market authorization have been slow. This has been due in part to a lack of standardization in cell manufacturing protocols, as well as a lack of biologically meaningful cell characterization tools and release assays. Cell production strategies to date have involved complex manual processing in an open environment which is costly, inefficient and poses risks of contamination. The NANT-001 bioreactor has been developed for the automated production of small to medium cell batches for autologous use. This is a closed, benchtop system which automatically performs several processes including cell seeding), media change, real-time monitoring of temperature, pH, cell confluence detachment. Here we describe a validation of the bioreactor in an environment compliant with current good manufacturing practice (cGMP) to confirm its utility in replacing standardized manual processing. Stromal vascular fraction (SVF) was isolated from lipoaspirate material obtained from healthy patients. SVF cells were seeded in the bioreactor. Cell processing was performed automatically and cell harvesting was triggered by computerized analysis of images captured by a travelling microscope positioned beneath the cell culture flask. For comparison, the same protocol was performed in parallel using manual methods. Critical quality attributes (CQA) assessed for cells from each process included cell yield, viability, surface immunophenotype, differentiation propensity, microbial sterility and endotoxin contamination. Cell yields from the bioreactor cultures were comparable in the manual and automated cultures and viability was >90% for both. Expression of surface markers were consistent with standards for adipose-derived stromal cell (ASC) phenotype. There were no differences in adipogenic or osteogenic differentiation propensity. Supernatants from all cultures tested negative for microbial and endotoxin contamination. Analysis of labor commitment indicated considerable economic advantage in the automated system in terms of operator, quality control, product release and management personnel. These data demonstrate that the NANT 001 bioreactor represents an effective option for small to medium scale, automated, closed expansion of ASCs from SVF and produces cell products with CQA equivalent to manual processes.